2021
DOI: 10.1021/acs.jpcc.1c07141
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Polarization and Doping in Ferroelectric In2Se3 Monolayers and Heterobilayers via Intrinsic Defect Engineering

Abstract: ferroelectric In 2 Se 3 with rarely discovered out-of-plane polarization has great potentials in advanced electronic and electromechanical applications. Considering that point defects are ineluctable in practical applications and may greatly influence the electronic properties, we systematically investigate the stability, induced conductive type, and electric polarization of defects in 2D In 2 Se 3 (D-In 2 Se 3 ) monolayers and In 2 Se 3 -graphene heterobilayers through first principles calculations. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…By calculating the position of both positive and negative charge centers, we were able to calculate the dipole moment of MX 2 monolayers. Former research ,, confirmed the validity of such an approach, and our calculation result of In 2 Se 3 is 0.0952 eÅ, which is considerably close to experimental data, further validating the results. The results of the calculated dipole moment showed great consistence with simulation results (Section II in SI for details).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…By calculating the position of both positive and negative charge centers, we were able to calculate the dipole moment of MX 2 monolayers. Former research ,, confirmed the validity of such an approach, and our calculation result of In 2 Se 3 is 0.0952 eÅ, which is considerably close to experimental data, further validating the results. The results of the calculated dipole moment showed great consistence with simulation results (Section II in SI for details).…”
Section: Resultssupporting
confidence: 86%
“…Such a strategy was applied in CrX 3 (X = F, Cl, Br, I) and successfully induced switchable polarization, demonstrating its feasibility of detecting possible multiferroic candidates . However, more subtle modulation effects on ferromagnetism and the feasibility on other magnetic monolayers remain unexplored . Before all explorations, the stability of ferromagnetic order in multiferroic monolayers fabricated with such a mechanism is supposed to be examined first.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to unveil the underlying mechanisms of analog and thermal tunable memristive behaviors, we performed first-principal calculations of formation energy and migration barrier of vacancies for pristine and sulfurized In 2 Se 3 . For easy visualization, here, we only investigate single selenium and sulfur vacancy formation, although more types of defects may be induced in reality . The selenium and sulfur atoms indicated by a circle in Figure a,b are deleted to raise a single vacancy.…”
Section: Resultsmentioning
confidence: 99%
“…For easy visualization, here, we only investigate single selenium and sulfur vacancy formation, although more types of defects may be induced in reality. 47 The selenium and sulfur atoms indicated by a circle in Figure 4a and chemical potential of selenium/sulfur element, respectively. We use the calculated energies of Se6 and S6 rings to estimate the chemical potential of selenium and sulfur, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…At this stage, the clear reason for this abnormal behavior is unknown, but it can be speculated that the various intrinsic defects, including vacancies, interstitials, and antisite defects, in In 2 Se 3 , seem to play complex roles as doping increases. Various intrinsic defects exist for this complex structure of α(2H)-In 2 Se 3 [24]. The complex phase change in In2Se3 may imply larger possibility of the intrinsic defects [19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%